ISOLATION OF FLUORESCENT PSEUDOMONAS STRAIN FROM TEMPERATE ZONE OF HIMACHAL PRADESH AND THEIR EVALUATION AS PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) - SHWETA SHARMA; MOHINDER KAUR; DURGA PRASHAD (The Bioscan, 2014)
A bacterial collection of 30 indigenous strains of Pseudomonas species were isolated from the normal and replant rhizospheric soil of apple and pear orchard of Kullu District temperate zone of Himachal Pradesh. Twenty three isolates from apple rhizospheric soil and seven isolates from pear rhizospheric soil were characterized on the basis of their morphological, physiological, biochemical and plant growth promoting activities. The strains were further studied on their ability to produce plant growth promoting activities such as plant growth hormone production viz., auxins, gibberellins and cytokinins, phosphate solubilizing activity, siderophore activity, protease enzyme activity, ammonia production, HCN production and antifungal activity. Auxins, gibberellins and cytokinins produced by isolates were in the range of 1.83-21μg/ml, 116.1-485.8 μg/ml and 63.6-90.0 μg/ml respectively. Pseudomonas isolates showed production of phosphate solubilizing activity in the range of 199.5 to 413.4 μg/ml available inorganic phosphate (Pi) and siderophore production in the range of 20-21 mm in plate assay and 67.27 %SU in liquid assay. Therefore, these results suggested that out of 30 isolates, two isolates An-1-kul and An-13- kul possessed multiple PGP (Plant growth promoting) traits thus can be further explored for its efficacy as effective PGPR (Plant growth promoting rhizobacteria).